Identifikasi dan Komposisi Hasil Tangkapan Purse Seine di Pelabuhan Perikanan Pantai Tamperan Kabupaten Pacitan, Jawa Timur - Ardiansah, Feri; Negara, I Ketut Wija; Pratiwi, Made Ayu (Current Trends in Aquatic Science; Vol 7 No 2 (2024), 2025)
Pacitan Regency is a district located in East Java Province. Pacitan waters have abundant pelagic fish resources with the main catch being flying fish and several other types of caught fish. One of the fishing tools used at PPP Tamperan Pacitan is the Purse Seine. The aim of this research is to identify purse seine catches and analyze the composition of purse seine catches. The research was conducted in April - May 2023. The method used in this research is a quantitative descriptive method by describing the object under study. Sampling was carried out by direct observation with a sample size of 21 vessels and the results obtained were 8 types of fish grouped into 6 orders, 5 families and 8 species. Results: The composition of the purse sein catch at PPP Tamperan is Flying Fish, Skipjack Fish and Tuna Fish as the most dominant fish caught. The percentage of fishermen's main catch is 96%, which includes Mackarel fish, skipjack, yellowfin tuna, and the percentage of by-catch is very small, namely 4%, which includes sunglir fish, lemadang, pogot and cumi. There is one species that has IUCN (Data Deficient) status, namely squid, which means that this species has insufficient data to be assessed in conservation status.